The reptile room - Snicket, Lemony; Helquist, Brett (New York : HarperCollinsPublishers, 1999)
After narrowly escaping the menacing clutches of the dastardly Count Olaf, the three Baudelaire orphans are taken in by a kindly herpetologist with whom they live happily for an all-too-brief time.
Booklist.
Pub Weekly.
School Library Journal.
6.1
5-8
Keywords: Baudelaire, Klaus (Fictitious character) -- Fiction; Baudelaire, Sunny (Fictitious character) -- Fiction; Baudelaire, Violet (Fictitious character) -- Fiction; Brothers and sisters -- Fiction; Humorous stories; Orphans -- Fiction; Baudelaire, Klaus (Fictional character) -- Fiction; Baudelaire, Sunny (Fictional character) -- Fiction; Baudelaire, Violet (Fictional character) -- Fiction; Humorous fiction; Orphans -- Fiction; Siblings -- Fiction